Finally, an Internationalization Policy for Canada - Desai-Trilokekar, Roopa; Jones, Glen (International Higher Education, 2013)
Canada is the only country in the OECD to not have a national strategy for international education. In 2011, the Canadian federal government announced plans to develop and launch Canada's first international education strategy, including the creation of an advisory panel. The panel's 2012 report outlines a balanced strategy to increase international student recruitment while also supporting the international mobility of Canadian students. Coordination of international education policy within a highly decentralized federal system remains a core challenge. Key words: International branch campus, cross-border higher education, internationalization.